Agrifood system employment: Innovations, policies, and knowledge gaps - Berdegué, Julio; Trivelli, Carolina; Vos, Rob (International Food Policy Research Institute, 2024)
Key messages: • Seven agriculture and agrifood value chain innovations are found to improve employment and income opportunities in the agrifood value chains. • Such income and employment require adequate enabling policies, including infrastructure investments, support to wholesale market development, social protection, labor market regulation, and supporting collective action organizations. • Eleven knowledge gaps need to be addressed to better inform agrifood system policy and investment decision-making.